PERAN MEDIA CERITA BERGAMBAR DALAM MENINGKATKAN KEMAMPUAN KOGNITIF ANAK PADA PROGRAM MOVING CLASS DI BBPMP PROVINSI JAWA BARAT - Nuranida, Siti; Suprapmanto, Joko (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to explore the use of illustrated storytelling media in improving the cognitive abilities of children aged 5-7 years through the Moving Class program at the BBPMP West Java Province. Early childhood is a crucial period for development, where children tend to be more open to visual-based learning. The method used is a qualitative descriptive approach involving 32 children and 8 teachers from four PAUD institutions as research subjects. Data collection techniques were carried out through observation, interviews, and questionnaires. The results of this study indicate that illustrated storytelling media plays a role in improving children's concentration, symbolic thinking skills, and understanding of the storyline. Children also demonstrated the ability to argue the content of the story with their daily experiences. The Moving Class program provides a flexible and fun learning environment, which supports the effectiveness of the media's use. Overall, it can be concluded that illustrated storytelling media is an educational tool that can improve children's thinking skills and early literacy skills in a comprehensive and meaningful way.